Characterizations and boron diffusion modelling on the AISI H13 steel - Ortiz-Domínguez M.; Keddam M.; Morales-Robles Á.J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A kinetic approach accounting for the linearity of boron profiles through the boronized layers on AISI H13 steel was developed. It aims to track the temporal evolution of the thicknesses of the FeB and (FeB + Fe2B) layers by considering new expressions for the mass balance equation at each growth front. These surface layers were generated by pack boronizing of AISI H13 steel in the temperature range of 1123 to 1273 K for duration ranging from 2 to 8 h. Finally, this linear model has been validated for two other sets of processing parameters (1323 K for 4.5 and 8.5 h). Iso-thickness diagrams were also proposed to optimize the thickness of the layers for targeted industrial usage.